2020
DOI: 10.1159/000506204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on Inflammation-Based Scores among Patients Diagnosed with Stage III Non-Small Cell Lung Cancer

Abstract: Background: Inflammatory and nutritional indexes are prognostic factors in non-small cell lung cancer (NSCLC). Furthermore, a low grade of chronic inflammation has been described in the older population (inflammaging). We aimed to evaluate the neutrophil-to-lymphocyte ratio (NLR), the Prognostic Nutritional Index (PNI), the advanced lung cancer inflammation index (ALI), the platelet-to-lymphocyte ratio (PLR), and the Glasgow Prognostic Score (GPS) in young and older patients diagnosed with locally advanced NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Further analysis confirmed the prognostic value of all these indicators, which were stratified by Kaplan-Meier curves. These findings are consistent with previous research in other tumors (20)(21)(22)(23)(24). One study (24) demonstrated the significance of the longitudinal assessment of ctDNA to predict response to anti-PD1 antibodies in metastatic melanoma, and the importance of persistent elevation of ctDNA on monitoring whole disease management.…”
Section: Discussionsupporting
confidence: 88%
“…Further analysis confirmed the prognostic value of all these indicators, which were stratified by Kaplan-Meier curves. These findings are consistent with previous research in other tumors (20)(21)(22)(23)(24). One study (24) demonstrated the significance of the longitudinal assessment of ctDNA to predict response to anti-PD1 antibodies in metastatic melanoma, and the importance of persistent elevation of ctDNA on monitoring whole disease management.…”
Section: Discussionsupporting
confidence: 88%
“…Palomar-Abril et al recently investigated this correlation in a cohort of 124 patients (84 young and 40 older) and found a higher median CRP, a lower hemoglobin level and leukocyte count and a lower prognostic nutritional index in the older cohort [50]. Unfortunately, the authors did not correlate these parameters with the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Palomar-Abril et al. noted that the prognostic role of ALI in NSCLC was not affected by age [ 89 ]. Furthermore, it is exciting that Mountzios et al.…”
Section: Albumin-related Inflammation Markers Based On Peripheral Blo...mentioning
confidence: 99%